Global Moral Standards as Viewed by the Thai Professionals - Bankoson, Vatt (International Journal of Publication and Social Studies, 2021)
A qualitative research aimed to synthesize and brainstorm global moral standards from the Thai professional viewpoints. Global moral standards as viewed by the Thai professionals have been developed based on the ideas across North America, Europe, Asia and Australia. The methods involve roundtable discussions gathered from 100 professional participants working in a government sector, a private sector, and a non-profit sector to resolve moral problems in a practical sense and to plan for moral standard policy. The results show that 1) Respect for the rights of people, others and organizations goes along with national constitutions; 2) Justice to everyone in organizations communicates with the public; 3) Responsibility for regular duties and impromptu situations establishes the mutuality of colleagues, organizations and the public; 4) Leadership shows high-patience, generosity, and bravery to the public; 5) Adaptability responds to possible changes, allowing human resources at all professions survive in society; 6) Dedication to quality serves nonstop service improvement; 7) Professionalism has equipped personnel resources with skills, knowhow, and speed to serve their public interests; and 8) Honesty with oneself, others, and organizations holds on the righteousness. To authorize universal moral standards in society, human and mind values projects are initiated.